Beyond the walls : a dialogue with Abraham Joshua Heschel and Edith Stein on the interreligious significance of empathy for Jewish-Christian understanding - Palmisano, Joseph Redfield (Irish School of Ecumenics, 2010)
The following thesis of approximately 94,000 words explores the interreligious significance of empathy for Jewish-Christian understanding. We examine how Edith Stein (1891-1942) responds to the call of empathy through a prophetic witnessing in theory and praxis in the midst of the Shoah, and incarnates a dialectical belonging between sameness and otherness. We employ a phenomenological methodology of‘reading’ Stein’s narrative through Abraham Joshua Heschel’s doctrine of divine pathos/prophetic sympathy. We explore how Stein, while incarnating a prophetic pathos, critically extends pathos/sympathy towards an em-pathos with the religious other. We argue that empathy may be a more nuanced, interreligiously attuned category for Jewish-Christian understanding and interreligious dialogue; a way of re-memhering oneself with the religious other that buttresses an interreligious unity-in-diversity as argued for in Vatican IPs Nostra Aetate.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin